The use of google translate by secondary school ESL learners in English language learning - Nair, Subadrah Madhawa; Ling, Angelina Lau Siew; Salleh, Nor Zalifah Abd Hamid @; Rajendran, Kalashini; Rani, Norhaslinda Abd; Apolonius, Lindey Easter (Edelweiss Applied Science and Technology, 2025)
This study explores how secondary school learners of English as a Second Language (ESL) use Google Translate (GT) in their language learning. Although digital tools are widely used in education, most existing research focuses on university students. Less is known about how ESL learners in secondary education use translation tools, especially those who are still developing their language skills. This study addresses that gap by investigating the perceived benefits and challenges of GT among secondary school learners. A qualitative research design was employed, grounded in the Technology Acceptance Model by Davis. Data were collected through semi-structured interviews with ten ESL learners aged 15 to 16 from a private secondary school in Kuala Selangor, Malaysia. The participants’ English proficiency ranged from average to low. Interviews were transcribed and analyzed thematically using Yin’s Five Phases of Data Analysis. Findings showed that learners used GT for its convenience and support in comprehension, particularly when reading or writing in English. However, participants also reported challenges related to accuracy, such as grammatical errors and mistranslations. Some learners developed an over-reliance on GT, using it without critical engagement. Despite these concerns, many participants demonstrated an awareness of its limitations and employed strategies such as cross-checking translations with other tools. These findings suggest that while GT can be a valuable resource, it should be used with guidance. Teachers play a key role in helping students apply it critically and responsibly. This study contributes practical insights for educators and adds to the growing body of research on technology-enhanced language learning, particularly for ESL learners in secondary education.